Marine shellfish exploitation as a means of reducing vulnerability to resource uncertainty in southern coastal Peru (200 BCE–150 CE). (December 2022) - Weinberg, Camille; Osborn, Jo; Espino Huaman, Richard
The effects of El Niño Southern Oscillation (ENSO) are notoriously hazardous for human populations of the hyperarid Peruvian coast. Yet, ENSO climate fluctuations are fundamental to the ecology of desert plant and animal resources that have been incorporated into human subsistence economies for millennia. We examine marine shellfish exploitation among early complex societies in southern coastal Peru at the end of the first millenium BCE to better understand the subsistence vulnerability of communities in arid environments with variable resource availability and productivity. We analyze new shellfish data from Jahuay, a shoreline fishing settlement in the Topará Quebrada occupied amidst new regional social hierarchies and intensifying inner-valley agriculture. We compare mollusk taxonomic diversity and taxa rank order with published assemblages from four near-contemporaneous sites to assess local and regional trends in resource exploitation. At Jahuay, a unique focus on foraging plentiful Donax obesulus clams resistant to ENSO effects may reflect a local buffering strategy to ensure a resource supply through interannual and decadal climate oscillations. Our comparative results suggest regional reliance on intertidal resource patches, especially rocky habitats, for consumable shellfish. The relative convenience of gathering sessile intertidal taxa that form dense settlements may partly explain their regional popularity. The potential to dry and exchange mollusk meat as a protein source likely enhanced diet diversification while supporting economic and social relationships between communities. Overall, our findings imply that mollusks and intertidal foraging landscapes were important within a broad-spectrum subsistence strategy suited to maintaining and coordinating food availability in a dynamic environment.